RELIGION AND EDUCATION : RELIGION AND EDUCATION - Chackalackal, Saju (Journal of Dharma, 2006)
“We are born human; but we become human.” That is, although physically all of us are born human, socially and culturally we have to become human beings through an arduous and lifelong process carried out within the human community. In fact, this becoming process cannot have a preset end, by the attainment of which the process can be halted or brought to an end. In spite of being an unending process, strategically, life should have proximate ends which we shall approach and realize individually and collectively through persistent and concerted efforts. It has to take into account not only the training of the intellect but also the will of human beings, as they have to balance and integrate the operations of these two vital faculties if they were to achieve a humane development. Therefore, the educative process that begins even before we are born forms and transforms us into beings that have a sense of meaning and value in life.